The use of social media for acquiring knowledge about an enterprise – a systematic literature review - Grzelak, Wojciech Remigiusz (Wykorzystanie mediów społecznościowych do pozyskiwania wiedzy o przedsiębiorstwie – systematyczny przegląd literatury, 2021)
The article explores the use of social media to gain knowledge about an enterprise. The study consists in a systematic literature review. The purpose of the literature analysis was to define and organise the terminology related to the use of social media to obtain knowledge about the enterprise. The study was divided into two phases. In the beginning, it was necessary to define the concept of social media, then use it to obtain knowledge about the company. In the second phase, an analysis of the use of the social media (SM) expression was carried out. The issue of an intelligent organisation – its concept and objectives – is discussed in this article. The paper presents the research and findings from the analysis of the literature on acquiring knowledge from social media, i.e. to define and organise the terminology related to the use of social media for the purpose of gaining knowledge about enterprises. The conclusion is that it is worthwhile to monitor the Internet and social media.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 4 (62), s. 10-24
Keywords: social media; knowledge about a company; user profile; media społecznościowe; zarządzanie wiedzą; systematyczny przegląd literatury